ANALISIS KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN LOMBOK TIMUR - Luthfi, Abrorni; Mulyono, Sugeng; Suswati, Endang; Sulaiman, Sulaiman (Universitas Hamzanwadi, 2023)
The aim of this research is to explore and describe the performance of East Lombok Regency DPRD Secretariat Employees. This research is a type of descriptive quantitative research. The population in this study was 79 East Lombok Regency DPRD secretariat employees consisting of 40 people with ASN status and 39 people with honorary staff status. The number of samples in this study was 64 in accordance with the number of questionnaires returned. The data analysis technique used in this research is the percentage technique. The research results show that; Performance Analysis of East Lombok Regency DPRD Secretariat Employees based on indicators of productivity, service quality, responsiveness and accountability falls into the